Long-term stability of physiological signals within fluctuations of brain state under urethane anesthesia - Nicholas R. G. Silver; Rachel Ward-Flanagan; Clayton T. Dickson (PLoS ONE, 2021)
Urethane, an acute laboratory anesthetic, produces distinct neurophysiological and physiological effects creating an effective model of the dynamics of natural sleep. As a model of both sleep-like neurophysiological activity and the downstream peripheral function urethane is used to model a variety of physiological and pathophysiological processes. As urethane is typically administered as a single-bolus dose, it is unclear the stability of peripheral physiological functions both within and between brain-states under urethane anesthesia. In this present study, we recorded respiration rate and heart rate concurrently with local field potentials from the neocortex and hippocampus to determine the stability of peripheral physiological functions within and between brain-states under urethane anesthesia. Our data shows electroencephalographic characteristics and breathing rate are remarkable stable over long-term recordings within minor reductions in heart rate on the same time scale. Our findings indicate that the use of urethane to model peripheral physiological functions associated with changing brain states are stable during long duration experiments.